Efektivitas Pembelajaran Pak Dengan Metode Stad Berbantuan Modul TTS Siswa Kelas VIII SMP Yoannes XXIII Semarang - Gregorius Sitohang; Hartutik Hartutik; Anselmus Joko Prayitno (Jurnal Filsafat dan Teologi Katolik, 2023)
The results of observations and interviews conducted showed that there were problems in Class VIII of SMP Yoannes XXIII Semarang, namely inappropriate methods and media, and the lack of student independence in learning. The main objective of this study was to examine the effectiveness of module-assisted STAD (Student Teams Achievement Division) learning in improving student learning outcomes in class VIII A, SMP Yoannes XXIII Semarang. This study used a quantitative experimental method with a pre-experimental type. From the data analysis, it was concluded that 1) there was an increase in student learning outcomes from a pre-test score of 51.35 to 84.42 in terms of student post-test data, 2). The application of the method is considered effective as seen from the N-Gain data in the experimental class of 70.2, 3) The regression test shows that student independence affects learning outcomes by 83.3%. The results of this study indicate that the application of the Student Team Achievement Division method assisted by the TTS module has proven to be successful in increasing student learning outcomes. Suggestions are that teachers are able to improve student learning outcomes using varied, appropriate methods and media and are able to follow student development according to the times.